2012
DOI: 10.1186/1742-2094-9-268
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF increases LPS-induced production of proinflammatory mediators via upregulation of TLR4 and CD14 in murine microglia

Abstract: BackgroundMicroglia are resident macrophage-like cells in the central nervous system (CNS) and cause innate immune responses via the LPS receptors, Toll-like receptor (TLR) 4 and CD14, in a variety of neuroinflammatory disorders including bacterial infection, Alzheimer’s disease, and amyotrophic lateral sclerosis. Granulocyte macrophage-colony stimulating factor (GM-CSF) activates microglia and induces inflammatory responses via binding to GM-CSF receptor complex composed of two different subunit GM-CSF recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
100
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 56 publications
4
100
0
Order By: Relevance
“…In this study, we showed that high potential of SKG T cells to produce GM-CSF produced a different outcome between zymosan-treated SKG and BALB/c. GM-CSF was reported to upregulate TLR2, TLR4, and CD14 expression (41)(42)(43) and boost IL-6 and IL-1b production from macrophages (41,44,45). Although serum concentration of GM-CSF in zymosan-treated SKG mice was very low and could not be detected by ELISA, we showed that GM-CSF could enhance the production of IL-6 and IL-1b by macrophages even at a low concentration (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…In this study, we showed that high potential of SKG T cells to produce GM-CSF produced a different outcome between zymosan-treated SKG and BALB/c. GM-CSF was reported to upregulate TLR2, TLR4, and CD14 expression (41)(42)(43) and boost IL-6 and IL-1b production from macrophages (41,44,45). Although serum concentration of GM-CSF in zymosan-treated SKG mice was very low and could not be detected by ELISA, we showed that GM-CSF could enhance the production of IL-6 and IL-1b by macrophages even at a low concentration (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Several lines of evidence have confirmed that systemic administration of LPS increases the production of inflammatory mediators including iNOS, COX2, and different cytokines such as TNF-α, IL-1β, and IL-6, which induce a number of neurobiological effects (PalssonMcDermott and O'Neill 2004;Parajuli et al 2012). Neuroinflammation has been shown to induce neurodegeneration in different forms of brain disorders such as sepsis, Alzheimer's disease, Parkinson's disease, and multiple sclerosis (Gao and Hong 2008;Lull and Block 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Our results showed that this concentration of AFB 1 could induce an inflammatory response on the human microglial cells, but it cannot convert them to the M2 phenotype of microglial cells. As the microglial cells act like a sensor of inflammation in the brain [32], it could be expected that the observed overexpression of TLRs is the reason for GM-CSF secretion in the AFB 1 -exposed microglia as a signal of danger for other resting microglial cells [33]; the increased GM-CSF can also lead to increased recruitment of inflammatory cells into the brain [34]. As such, GM-CSF could simply induce microglial cell proliferation [35], further boosting the proinflammatory/toxic/dysregulatory microenvironment in the brain.…”
Section: Discussionmentioning
confidence: 99%